ANALISIS HUKUM PIDANA ADAT DALAM HUKUM PIDANA NASIONAL - Handayani, Tri Astuti; Prabowo, Andrianto (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
This research aims to analyze the position of customary criminal law in national criminal law. National criminal law in Indonesia is the legal framework that regulates criminal acts throughout the country. The Criminal Code (KUHP) is the main criminal law basis which provides norms and sanctions for various types of criminal acts. This legal research method is normative legal research which carries out library research. The specification of this research is that the research method used is analytical descriptive. The source and type of research data is secondary data consisting of primary and secondary legal materials. The data analysis method was carried out normatively. The results of this research show that the position of customary criminal law in national criminal law creates complex and varying dynamics depending on a country's legal approach and policies. In general, customary criminal law has a relatively separate position in national criminal law, often recognized as part of local cultural heritage and traditions. However, challenges arise in integrating customary criminal law with national criminal law to achieve a balance between cultural diversity and the protection of human rights.